Studies on oxidative stress caused by Cu and Zn excess in germinating seeds of Indian mustard (Brassica juncea L.) - Szőllősi, Réka (Acta Biologica Szegediensis, 2011)
Seeds of Indian mustard were germinated at 0, 50, 100, 200 mg/L Cu and Zn concentrations, in dark for 12, 24, 48 and 96 h, at 24p1oC. The real metal content in seeds was determined by AAS. For biochemical measurements fresh material were homogenized and the supernatant was used for all assays. The following parameters were evaluated: FRAP (ferric reducing ability of plasma), lipid peroxidation (LP), glutathione (GSH), total protein content, GST (glutathione-S-transferase), GPOX (guaiacol peroxidase) and CAT (catalase).